The Body Shape Questionnaire Is Not Invariant Across Sex: Evidence From Portuguese-Speaking University Students. Issue 3 (June 2019) - da Silva, Wanderson Roberto; Swami, Viren; Nogueira Neves, Angela; Marôco, João; Ochner, Christopher N.; Alvares Duarte Bonini Campos, Juliana
The Body Shape Questionnaire (BSQ) is a widely used measure of body shape concerns that was originally designed for use with women but has more recently been used with boys and men. The latter use may be problematic, given that no previous study has demonstrated sex invariance for BSQ scores. To determine the extent to which BSQ scores are sex invariant, we asked Portuguese-speaking women ( n = 1, 613) and men ( n = 871) to complete the full BSQ (34 items). Confirmatory factor analysis indicated that a hypothesized 32-item model of BSQ scores and shorter versions had acceptable fit indices in women and men, separately. However, multigroup confirmatory factor analysis showed that these BSQ model scores had configural but not metric, scalar, or strict sex invariance. Differential item analysis indicated significant item-functioning differences on 19 of the 32 retained BSQ items. Thus, BSQ scores are not sex invariant, making problematic the results of previous studies that have compared latent BSQ scores across sex.